Protective effect of Huanglian Pingwei San on DSS-induced ulcerative colitis in mice through amelioration of the inflammatory response and oxidative stress - Dong, Gengting; Pang, Xiaoyan; Wang, Ximin; Peng, Lin; Xiao, Qili; Guo, Shunan; Dai, Weibo (Frontiers in Pharmacology, 2024)
Introduction Ulcerative colitis (UC) results in the breakdown of the mucosal barrier caused by persistent inflammation and oxidative stress. Huanglian Pingwei San (HLPWS) is a commonly prescribed traditional Chinese medicine for treating colitis, but the precise mechanism remains unclear. The aim of this study was to systematically investigate the protective effect of HLPWS on UC mice and to elucidate the underlying mechanisms involved. Materials UC mouse model was established in C57BL/6 mice via 2.25% dextran sulfate sodium (DSS). The chemical composition of HLPWS was examined through UPLC/MS Q-TOF analysis. The efficacy of HLPWS in treating UC was assessed. A TUNEL assay was used to detect apoptotic cells. An ELISA was used to evaluate the levels of inflammatory cytokines in colon tissues and serum. The percentages of Treg and Th17 cells were measured via flow cytometry. The protein expression in the colonic tissue was validated via immunohistochemistry (IHC) and Western blotting. Results HLPWS significantly improved UC symptoms and colon tissue histology in mice. The structure and function of the intestinal barrier were restored by HLPWS treatment, as shown by increased DAO content, reduced levels of FITC-dextran, and increased protein expression of ZO-1, occludin, claudin, and MUC2. HLPWS dose-dependently decreased the number of apoptotic cells by inhibiting P53, P21, P27, cleaved caspase 3, and p-H2AX expression. HLPWS also reduced abnormal oxidative stress by reducing Keap1 expression and increasing Nrf2 and HO-1 levels. Furthermore, HLPWS rebalanced the Treg/Th17 ratio to alleviated inflammatory reactions in UC mice. Conclusion These findings suggest that HLPWS alleviated colonic intestinal barrier dysfunction in UC mice by reducing oxidative stress and restoring immune balance. This study underscores the potential therapeutic benefits of HLPWS and highlights its potential as a future pharmaceutical candidate for UC treatment.